Interfaces in solid-state sodium-ion batteries: NaCoO2 thin films on solid electrolyte substrates. (1st April 2018) - Guhl, Conrad; Kehne, Philipp; Ma, Qianli; Tietz, Frank; Komissinskiy, Philipp; Jaegermann, Wolfram; Hausbrand, René
Abstract: On the way to sodium-based all-solid-state batteries, interface analysis is a key issue. In this work, the interface between two typical solid sodium-ion conductors (Na-β″-Al2 O3 and NASICON) and the layered oxide material NaCoO2 is investigated. The formation of the interface between the electrolyte material and the NaCoO2 coating is studied using an in-situ X-ray photoemission spectroscopy (XPS) surface science approach. Only a slight reduction of zirconium and scandium in NASICON was observed in proximity to the cathode side interface, while severe reactions, including the formation of a CaOAl2 O3 mixed phase, were detected between Na-β″-Al2 O3 and NaCoO2 . Highlights: Interface chemistry between electrolyte and cathode material. All-solid-state battery interfaces. Formation of reaction phase at the solid electrolyte cathode interface. CaNa ion exchange.